Career Guidance Advocacy Program and The Grade 10 Completers’ Career Choice - Maestrado, Julie T.; Bucar, Jimmy D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Upon entering senior high school, students choose a career track. School counselors/designates through the career guidance advocacy activities play a vital role in student’s readiness for related career decision. With this, the study determined the extent of implementation of the Career Guidance Advocacy Program and its relation to the actual career choice of the Senior High School students. A descriptive correlational research design using documentary data was utilized and conducted in 60 selected public secondary schools in the Division of Bohol which involved 1,200 Grade 11&12 students enrolled in school year 2019-2020; with 60 guidance counselors/designates and 60 homeroom advisers. The instrument used were adapted and modified by the researcher based on the guidelines stipulated in Enhance Basic Education Act of 2013; DepEd Order No. 41, series of 2015, and Developing for National Standard for School Counseling in the Philippines questionnaire by Clemeña 2010. The result showed that educational qualification, job description, years of experience, lack of training and resources and time constrained affect the conduct of the career guidance activities. For the actual choice of the students, the majority were not able to follow the NCAE result due to a lot of intervening factors. The test of correlation revealed that the career guidance activities did not directly relate with the choices of the students. Hence, areas for enhancement of the career guidance advocacy program were put forward.